Paranormal activity 3 [videorecording (DVD)] - Joost, Henry; Schulman, Ariel; Csengery, Chloe, 2000-; Brown, Jessica Tyler; Featherston, Katie; Ephraim, Molly (Paramount Home Entertainment, 2012)
In 1988, young sisters Katie and Kristi befriend an invisible entity who resides in their home.